Selective laser sintering manufacturing of polycaprolactone bone scaffolds for applications in bone tissue engineering. Issue 4 (15th June 2015) - Mazzoli, Alida; Ferretti, C; Gigante, A; Salvolini, E; Mattioli-Belmonte, M
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to show how selective laser sintering (SLS) manufacturing of bioresorbable scaffolds is used for applications in bone tissue engineering. Design/methodology/approach – Polycaprolactone (PCL) scaffolds were computationally designed and then fabricated via SLS for applications in bone and cartilage repair. Findings – Preliminary biocompatibility data were acquired using human mesenchymal stem cells (hMSCs) assuring a satisfactory scaffold colonization by hMSCs. Originality/value – A promising procedure for producing porous scaffolds for the repair of skeletal defects, in tissue engineering applications, was developed.